INVESTIGATION OF EWOM ON GREEN PRODUCT PURCHASE INTENTION AMONG GEN Z : INTEGRATING OF EWOM ADOPTION - Toni Ahmad Subekti; Fitra Mulya; Junifar Akmal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to investigate the influence of eWOM on social media on green product purchase intention among Generation Z. This study integrates two adoption models into a conceptual framework. A quantitative research design was used to collect data from 300 Generation Z respondents through a structured questionnaire distributed online via Google Forms. Data analysis was conducted using SmartPLS 4.0, which included testing the validity and reliability of the measurement model (outler) and structural model (inner) to evaluate path coefficients and test hypotheses. The results showed that eWOM Quality, need of eWOM and attitude toward eWOM positively influenced eWOM usefulness, but eWOM Quantity and eWOM Credibility did not affect the influence of eWOM usefulness. eWOM Credibility, eWOM Quantity, Need of eWOM and attitude toward eWOM positively influenced eWOM Adoption. Furthermore, eWOM usefulness showed significant impact on eWOM adoption and green purchase intention among gen Z consumers. The conceptual framework in this study offers significant managerial implications as it identifies key elements of eWOM reviews that positively influence Gen Z intentions.